PEMBERDAYAAN MASYARAKAT DESA MENUJU PENCAPAIAN SDGS MELALUI INOVASI PRODUK LOKAL (TEH RAMBUT JAGUNG) DAN PENGUATAN LITERASI KESEHATAN - Rahmawati Mansur; Miranda; Muthia Oktaviani Hadju; Nursaifa Sari Gafar; Putu Arya Satya Mahaputra; Shalaisa Amani Fatiha; Sahrul A. Harun; Yustin Abdullah (STKIP Subang, 2026)
The Sustainable Development Goals (SDGs) have become a global framework adopted by the Indonesian government down to the village level. This community service research (PkM) aims to empower the community of Datahu Village, Anggrek District, North Gorontalo Regency through the Independent Work Study (KKM) program, in integrating local product innovation and strengthening health literacy as concrete efforts to achieve SDG 3: Good Health, SDG 8: Decent Work and Economic Growth, and SDG 12: Responsible Consumption and Production. The focus of innovation is the utilization of agricultural waste, namely corn silk, into herbal tea products with economic value and to control non-communicable diseases. Meanwhile, strengthening health literacy includes education on monitoring the nutritional status of infants, introduction to Family Medicinal Plants (TOGA), education on drug logos, Clean and Healthy Living Behaviors (PHBS), and anti-bullying prevention. The PkM method used is Asset-Based Community Development (ABCD) through three main stages: potential assessment, program implementation (training and education), and evaluation. The results of the activities show a significant increase in the community's knowledge and skills in processing corn silk tea, as well as an increase in awareness and practice of PHBS and infant nutrition monitoring.